Fruit Characteristics of Some Traditional Pear Varieties in the Prespa Region. - Selamovska,Ana; Miskoska-Milevska,Elizabeta; Najdenovska,Olga; Canev,Ile (University of Kragujevac, Faculty of Agronomy, Cacak, 2015)
The aim of this study was the evaluation of phonological, fruit and chemical characteristics of 6 traditional pear varieties ('Mustabej', 'Patliganka', 'Ljubichica', 'Tatlikuti', 'Shaldanka' and 'Ekshikuti') typical of the Prespa region in Macedonia. These varieties flowered in the second half of April up until the end of April. 'Shaldanka' and 'Ekshikuti' flowered the earliest. According to ripening time, 'Mustabej' was characterized as a summer variety, 'Patliganka' and 'Ljubichica' as autumn varieties, 'Tatlikuti' and 'Shaldanka' as late-autumn varieties, and 'Ekshikuti' as a winter variety. These varieties had a medium-long fruit stalk except 'Tatlikuti'. All varieties contained a low quantity of seeds in the fruit. The biggest fruits, with the longest fruit stalk and the highest value of stone cells were characteristic of 'Shaldanka'. 'Mustabej' had the highest value for fruit firmness. 'Tatlikuti' formed fruits with the best flavor.
Keywords: pear, traditional variety, fruit characteristics, Prespa region, Macedonia